Infection by multidrug-resistant Elizabethkingia meningoseptica: case reports - Jailton Lobo da Costa Lima; Giwellington Silva Albuquerque; Lílian Rodrigues Alves; Kaliny Benicio Torres; Luciana Rezende Bandeira de Mello; Polliana Guabiraba e Silva Cavalcanti; Paulo Sérgio Ramos Araújo; Maria Amélia Vieira Maciel (Sociedade Brasileira de Patologia Clínica, 2014)
We report two cases of sepsis in critically ill patients in two tertiary care hospitals in Recife-PE, Brazil. The first case is an 87-year-old patient with chronic myeloid leukemia and sepsis; and the second case is a 93-year-old patient with prostate cancer and septic shock caused by multidrug-resistant (MDR) Elizabethkingia meningoseptica.